1997
DOI: 10.1046/j.1365-2249.1997.d01-1024.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcium channel blockers suppress the contact hypersensitivity reaction (CHR) by inhibiting antigen transport and presentation by epidermal Langerhans cells in mice

Abstract: SUMMARYSince Langerhans cells (LC) are the principal antigen-presenting cells among epidermal cells, treatments suppressing LC function may inhibit CHR. Although calcium channel blockers (CCB) have been shown to suppress the functions of several immunologically active cells, little is known about their effect on LC. In this study we show that pretreatment with topical 1% nifedipine or verapamil HCl significantly suppressed both the sensitization and elicitation phases of a CHR in mice. We then investigated whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…41,42 Data reported in the present study cannot justify this assumption, and further studies are required to explain the mechanism of healing of fissure. However, the subsequent formation of an inflammatory infiltrate from a chronic anal fissure is associated with continuous hypertonicity of the internal sphincter, a microcirculatory disturbance, 3 and the presence of fibrosis and myositis throughout the internal anal sphincter.…”
mentioning
confidence: 55%
“…41,42 Data reported in the present study cannot justify this assumption, and further studies are required to explain the mechanism of healing of fissure. However, the subsequent formation of an inflammatory infiltrate from a chronic anal fissure is associated with continuous hypertonicity of the internal sphincter, a microcirculatory disturbance, 3 and the presence of fibrosis and myositis throughout the internal anal sphincter.…”
mentioning
confidence: 55%
“…Interestingly, while in human monocyte-derived DCs the L-type VDCC inhibitor nifedipine was reported to block both engulfment of apoptotic bodies and IL-12 production induced by lectin-crosslinking (Poggi et al, 1998), murine BM-DCs were shown to lack VDCC activity (Hsu et al, 2001). Notably, nifedipine was reported to inhibit the maturation of murine LCs (Katoh et al, 1997), which prompted us to apply this inhibitor during stimulation of SP37A3 cells. In contrast to the findings of Katoh et al (1997) for LCs, inhibition of L-type VDCCs in SP37A3 cells exerted no detrimental effects on the stimulation-associated acquisition of potent T cell stimulatory capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, nifedipine was reported to inhibit the maturation of murine LCs (Katoh et al, 1997), which prompted us to apply this inhibitor during stimulation of SP37A3 cells. In contrast to the findings of Katoh et al (1997) for LCs, inhibition of L-type VDCCs in SP37A3 cells exerted no detrimental effects on the stimulation-associated acquisition of potent T cell stimulatory capacity. Taken together, these results show that the various DC populations greatly differ in the functional activity of Ca 2+ channel types during DC stimulation, and accordingly in the qualitative contribution of these Ca 2+ channels to DC maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Just how DHPs mobilize Ca 2ϩ is unclear. Nevertheless, the signaling pathway deserves further attention because nifedipine has been found to modulate numerous DC functions, including inhibition of Ag processing (42), apoptotic body engulfment, and IL-12 secretion (26).…”
Section: Discussionmentioning
confidence: 99%